2006
DOI: 10.1021/om0602613
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabenzo[a,c,g,i]fluorenyllithium and η5-Tetrabenzo[a,c,g,i]fluorenyltitanium Complexes

Abstract: Tetrabenzo[a,c,g,i]fluorene (Tbf-H, 4) was deprotonated with n-butyllithium, leading to ionic Tbf-LiLn complexes 5 and 6, consisting of well-separated cations (Li(THF)4 (5), Li(DME)3 (6)) and Tbf anions. Subsequent reactions with chlorotitanium alkoxides Cl x Ti(O i Pr)4 - x (x = 1, 3) and chlorotitanium phenoxides {ClTi(OR)3(THF)}2 (R = C6H5 (12), 4-MeC6H4 (13), 4- t BuC6H4 (14)) give a series of η5-tetrabenzo[a,c,g,i]fluorenyltitanium complexes (TbfTiCl2(O i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
2
21
0
1
Order By: Relevance
“…Vor kurzem berichteten Beckhaus et al. über die Koordinationschemie von Tetrabenzo[ a , c , g , i ]fluoren 11…”
Section: Methodsunclassified
“…Vor kurzem berichteten Beckhaus et al. über die Koordinationschemie von Tetrabenzo[ a , c , g , i ]fluoren 11…”
Section: Methodsunclassified
“…DBFs have a broad steric obstruction (with a non-planner structure) due to the distortion of the skeleton itself, thus inhibiting guest quenching concentration and may be doped at a high concentration which also inhibits excimer light emission. The DBFs also have large amorphism due to distortion of the skeleton itself and can thus form light emitting layers with adequate film characteristics [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…3 Later, a crystallographic analysis of 2 revealed that the TBF framework has a nonplanar helicene-like structure in the crystals. 4 We recently synthesized a series of 17,17-dialkyltetrabenzofluorenes 3 (R = methyl to hexyl) that show intense blue fluorescence, not only in solution, but also in the solid state. 5 Moreover, we have reported unique fluorescence properties for 3,14-bis(4-nitrophenyl)-17,17-dipentyl-17H-tetrabenzo[a,c,g,i]fluorene.…”
mentioning
confidence: 99%
“…An X-ray crystallographic analysis of the cocrystal surprisingly showed that its crystal parameters 10 were almost identical to those of a known crystal of 2. 4 The TBF moieties in 2 and 4 have the same helicene-like structure with a C 2 symmetry in the co-crystal; the spatial relationship between the carbonyl group in 2 and the methylene group in 4 is disordered statistically in the molecular SYNLETT0 9 3 6 -5 2 1 4 1 4 3 7 -2 0 9 6 © Georg Thieme Verlag Stuttgart • New York 2016, 27, 2085-2090 cluster Cluster Syn lett structure. Figure 2 shows an ORTEP drawing of 4 and the molecular packing of 2 and 4.…”
mentioning
confidence: 99%